English-into-Arabic Subtitling of Swearwords: Kevin Hart’s Comedy Movies as a Case Study - Ali, Dania Abbas M (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The present study is concerned with the analysis of profane words uttered by characters in comedy movies starred by Kevin Hart. The research aims at identifying the semantic shifts of SWs in the Arabic subtitles of the selected movies and the possible causes of these shifts. In addition, it is devoted to diagnosing the changes in the pragmatic functions of SWs in the subtitles in comparison with those in the movies, specifying the translation strategies used by amateur subtitlers when subtitling SWs in the selected corpus into Arabic. The difficulty that the study tries to find a solution to is that subtitlers tend to omit swearwords or tone them down with less interest of the contextual meaning of the words. Although there are many studies conducted on swearing in the subtitles, there are not so many studies concerned with the semantic shifts between the source and the target text. It is hypothesized that in subtitling comedy movies, literal translation is mainly avoided to bridge the cultural differences between both speech communities since it involves introducing harsh and offensive subtitled swearwords. Besides, target language receivers may consider some words offensive which are not so in the movies due to cultural differences. In subtitling swearwords in comedy movies, it has been evidenced that subtitlers are mainly concerned with conveying the messages behind the words uttered by characters as far as possible. And at the same time, offensive words are typically subtitled non-literally owing to the fact that literal translation sometimes conveys harsh and socially undigested expressions. A lot of subtitled swearwords were regarded by TL receivers as non-profane words and expressions. The reverse happens in that TL readers watching the subtitled comedy movies consider some words as being socially rejected while they are not so in the original spoken text. This is attributed to cultural differences between the two languages.